Small Farm Survival in Greece, Italy and Portugal. (April 2014) - Salvioni, Cristina; Papadopoulou, Eleni; Santos, Maria Dos
Summary Until the end of the 20th century, farming in Greece, Italy and Portugal was characterised by inflexible land and labour markets and thus had persistently high proportions of small farms and aged holders. Over time, several policy interventions in these countries have aimed at increasing average farm size. Nevertheless, small farms still account for a very large percentage of all holdings, due to institutional, social and market factors. Small farms are mainly concentrated in two kinds of area. First, mountainous and economically depressed inland regions where outmigration has often resulted more in farmland abandonment rather than in land concentration. Second, peri‐urban areas and other economically diversified rural contexts where many small farms survive thanks to the adoption of household strategies based on pluriactivity and outsourcing. Although it is still difficult to predict the impact of the current recession on small farms, it is possible to distinguish two emerging trajectories. In one, reduced chances of off‐farm work may challenge the resilience of pluriactive small farms. Former pluriactive farmers may focus on scale economies in order to increase their farming incomes. On the other, small‐scale farming is increasingly relied on for household budgets and food security, and could cause a 'return to the land'.